1997
DOI: 10.1101/gad.11.6.738
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a cAMP-responsive activator reveals a two-component mechanism for transcriptional induction via signal-dependent factors.

Abstract: We have examined the mechanism by which the cAMP-responsive factor CREB stimulates target gene expression following its phosphorylation at Ser-133. Using an in vitro transcription assay, we found that two signals were required for target gene activation: a phospho(Ser-133)-dependent interaction of CREB with RNA polymerase II via the coactivator CBP and a glutamine-rich domain interaction with TFIID via hTAF(II)130. The adenovirus E1A oncoprotein was found to inhibit phospho(Ser-133) CREB activity by binding to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
205
2
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(217 citation statements)
references
References 28 publications
9
205
2
1
Order By: Relevance
“…(b) Western blot analysis of nuclear extract from A431 cells using anti-BRCA1 antibody after immunoprecipitation with anti-BRCA1 antibody was done as described (Cui et al, 1998b). The protein bands shown represent endogenous BRCA1a (p110) and BRCA1b (p100) proteins BRCA1 associates with RNA polymerase II holoenzyme complex (Scully et al, 1997a) and CBP (CREBbinding protein) is a component of the holoenzyme (Nakajima et al, 1997). Previously, we have found BRCA1a/p110 and BRCA1b/p100 to interact both in vitro and in vivo with the carboxy-terminal domain of transcription factor CBP (Cui et al, 1998b).…”
mentioning
confidence: 99%
“…(b) Western blot analysis of nuclear extract from A431 cells using anti-BRCA1 antibody after immunoprecipitation with anti-BRCA1 antibody was done as described (Cui et al, 1998b). The protein bands shown represent endogenous BRCA1a (p110) and BRCA1b (p100) proteins BRCA1 associates with RNA polymerase II holoenzyme complex (Scully et al, 1997a) and CBP (CREBbinding protein) is a component of the holoenzyme (Nakajima et al, 1997). Previously, we have found BRCA1a/p110 and BRCA1b/p100 to interact both in vitro and in vivo with the carboxy-terminal domain of transcription factor CBP (Cui et al, 1998b).…”
mentioning
confidence: 99%
“…An increasing body of results also shows that hTAF II 28, hTAF II 135, and hTAF II 105 can act as specific transcriptional coactivators in mammalian cells. Expression of hTAF II 135 specifically potentiates activation by the liganddependent activation function 2 (AF-2) of the nuclear receptors (NRs) for all-trans retinoic acid (retinoic acid receptor), thyroid hormone (thyroid hormone receptor), and vitamin D 3 (vitamin D 3 receptor [VDR]) (24).…”
mentioning
confidence: 99%
“…Expression of hTAF II 135 specifically potentiates activation by the liganddependent activation function 2 (AF-2) of the nuclear receptors (NRs) for all-trans retinoic acid (retinoic acid receptor), thyroid hormone (thyroid hormone receptor), and vitamin D 3 (vitamin D 3 receptor [VDR]) (24). Distinct domains of hTAF II 135 interact specifically with Sp1, CREB, and E1A, and coexpression of the TAF II 135 domains with which these activators interact has a dominant negative effect on their activity (23,28,33,36).…”
mentioning
confidence: 99%
“…Since mutation of Thr69 and Thr71 dramatically reduces the basal activity of the ATF2 N-terminus, these two residues might be essential for the interaction of ATF2 with basal transcription factors. In this respect it is interesting to note that transactivation by the cAMP-inducible transcription factor CREB seems to require interactions of CREB with both CBP (following phosphorylation of CREB on Ser133) and TAFII130 (Nakajima et al, 1997). It might be that also in the case of ATF2 two independent protein-protein interactions are involved in transactivation.…”
Section: Discussionmentioning
confidence: 99%
“…cJun) of phosphorylation of the transcription factors (Chrivia et al, 1993;Kwok et al, 1994;. CBP can also associate with the basal transcription factor TFIIB (Kwok et al, 1994) and with the RNA polymerase II complex (Kee et al, 1996;Nakajima et al, 1997), whereas p300 has been shown to interact either directly or indirectly with the TATA-box-binding protein (TBP) (Abraham et al, 1993). Through their interactions with transcription factors, p300 and CBP are thought to upregulate transcription by recruiting the basal transcription apparatus to p300/CBP responsive promoters.…”
Section: Introductionmentioning
confidence: 99%